Clinical characteristics and prognosis of anti-MDA5 antibody positive dermatomyositis patients with secondary interstitial lung disease - MA Zongbo; ZHAO Cheng; QIN Fang; CHEN Zhanrui; PAN Dongmei; ZENG Wen; LIAO Xiaoling; LEI Ling (Guangxi Yike Daxue xuebao)
Objective To analyze the clinical characteristics and prognostic factors of anti-melanoma differentiation-associated gene 5 (MDA5)-positive dermatomyositis (DM) patients with secondary interstitial lung disease (ILD). Methods A retrospective collection was conducted on 97 patients with DM-ILD admitted to the First Affiliated Hospital of Guangxi Medical University from January 2018 to December 2022. They were divided into anti-MDA5 positive group and anti-MDA5 negative group. The clinical characteristics and survival rate of the two groups were compared, and the influencing factors of prognosis were analyzed. Results Compared with the anti-MDA5 negative group, the disease duration of the anti-MDA5 positive group was shorter, the proportion of chest tightness, rapid progress (RP)-ILD, pulmonary infection and skin ulcers was increased, the proportion of pulmonary arterial hypertension (PAH) was decreased, the levels of white blood cells, platelets and creatine kinase were decreased, and the serum ferritin levels were increased (all P < 0.05). Compared with the anti-MDA5 negative group, the proportions of combination of two immunosuppressants, use of gamma globulin and the first use of antibiotics during hospitalization were higher in the anti-MDA5 positive group (all P < 0.05). With a median follow-up of 17.5 months, the overall mortality rate of anti-MDA5 positive group was 45.5%, and the 6-month, 12-month and 36-month survival rates were 61.43%, 58.57% and 55.71%, respectively. Cox regression analysis showed that the risk factors for the prognosis of anti-MDA5 positive ILD were RP-ILD, Velcro rales and elevated carcinoembryonic antigen (CEA) (all P < 0.05). Conclusion Patients with anti-MDA5 positive ILD have a shorter disease duration. They are prone to skin ulcers and lung infections, have a low incidence of PAH, and have a high proportion of immunosuppressive agents combination and antibiotic use. The occurrence of RPILD, Velcro rales, and elevated CEA are risk factors for prognosis.